ADDRESS TERMS IN DIPLOMATIC INTERACTION: A SOCIOLINGUISTIC STUDY OF TRUMP-ZELENSKYY CONFRONTATION - Simanjuntak, Juni Santa; Sinaga, Muhammad Hidayatullah Tuahta; Trifena, Atalya; Rangkuti, Rahmadsyah (Linguistics and Literature Journal, 2025)
This study examined the use of address terms in high-stakes diplomatic interaction, focusing on the meeting between President Donald Trump and President Volodymyr Zelenskyy in the Oval Office on February 28, 2025. The research was important because address terms in diplomacy are not only markers of etiquette but also strategies that shape perceptions of authority, politeness, and legitimacy. The purpose of the study was to analyze how address terms shifted between formal and confrontational segments of the interaction and to explore the implications of these shifts for understanding power dynamics in political communication. A qualitative research design was employed, utilizing discourse analysis of transcripts and recordings from the event. Data were segmented into formal introductions and confrontational exchanges, coded according to the type of address term used, and interpreted through the lens of sociolinguistic variation. The findings revealed that formal address terms dominated the opening exchanges, reflecting ritualized respect and protocol. However, during confrontational moments, speakers increasingly employed direct pronouns and informal references, though formal titles did not disappear entirely. Instead, alternation between formal and direct address was observed, indicating strategic language use under rhetorical pressure. The study concluded that address terms in diplomatic contexts functioned as dynamic rhetorical tools rather than static markers of formality. This demonstrated that shifts in address terms were not merely linguistic preferences but deliberate strategies employed to negotiate authority, face, and legitimacy in international diplomacy.Keywords: address terms, diplomatic interaction, sociolinguistics, political communication, variation theory